2018
DOI: 10.1056/nejmoa1800781
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Cardioverter–Defibrillator after Myocardial Infarction

Abstract: BACKGROUND Despite the high rate of sudden death after myocardial infarction among patients with a low ejection fraction, implantable cardioverter-defibrillators are contraindi-cated until 40 to 90 days after myocardial infarction. Whether a wearable cardio- verter-defibrillator would reduce the incidence of sudden death during this high-risk period is unclear. METHODS We randomly assigned (in a 2:1 ratio) patients with acute myocardial infarction and an ejection fraction of 35% or less to receive a wearable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
232
4
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(258 citation statements)
references
References 40 publications
(33 reference statements)
10
232
4
12
Order By: Relevance
“…Notwithstanding, based on the findings depicted herein, MRAs could be considered in patients with a MI and an EF around 40%. The event rate reduction is marked in the first few months of therapy initiation (and may be maintained thereafter), this is of particular relevance because MRAs may reduce the risk of sudden death in this “high‐risk” post‐MI period were defibrillators are not indicated . The ongoing Colchicine and Spironolactone in Patients With STEMI/SYNERGY Stent Registry (CLEAR‐SYNERGY) trial (http://clinicaltrials.gov Identifier: NCT03048825) may help in assessing the potential effect of MRAs in patients with MI and an EF ≥ 40%.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, based on the findings depicted herein, MRAs could be considered in patients with a MI and an EF around 40%. The event rate reduction is marked in the first few months of therapy initiation (and may be maintained thereafter), this is of particular relevance because MRAs may reduce the risk of sudden death in this “high‐risk” post‐MI period were defibrillators are not indicated . The ongoing Colchicine and Spironolactone in Patients With STEMI/SYNERGY Stent Registry (CLEAR‐SYNERGY) trial (http://clinicaltrials.gov Identifier: NCT03048825) may help in assessing the potential effect of MRAs in patients with MI and an EF ≥ 40%.…”
Section: Discussionmentioning
confidence: 99%
“…Data from the Prospective Registry of Patient Using the Wearable Defibrillator (WEARIT‐II) Registry demonstrated a high rate (3% for 3 months) of sustained ventricular tachyarrhythmia at high‐risk patients, and suggested WCD to be safe and effective in protecting patients at risk of SCA . The Vest Prevention of Early Sudden Death Trial was a recent multicenter, randomized, controlled trial, and it also demonstrated that WCD reduced all‐cause death rate when comparing to the control group without WCD (3.1% vs 4.9%; P < .05) …”
Section: Introductionmentioning
confidence: 99%
“…A noninvasive monitoring strategy such as CABs that can be shown to guide medical therapies in such a manner that rehospitalizations are reduced would provide significant value to patients and to the healthcare system. In such a case, addition of CAB measurements to WCDs would provide additional incentives for patients to comply with WCD use; it comes as no surprise that compliance with WCD is key to its ability to prevent sudden cardiac death (Olgin et al, ; Reek et al, ) and limits the potential benefit for some patients.…”
Section: Discussionmentioning
confidence: 99%